Enhanced production of alkaline protease by Teredinobacter turnirae in fed-batch feremntation using a concentrated medium - Beshay, Usama (Array, 2008)
To increase cell concentration and the production of alkaline protease, fed-batch cultures with standard medium (1x) or concentrated medium (2x or 5x) as feed were performed. In a fed-batch culture with standard medium as feed, the biomass concentration reached 9.6 g L–1 and the protease activity obtained was 8500 U mL–1 compared to 3000 U mL–1 obtained by growing Teredinobacter turnirae cells with standard PB-medium in batch culture. For further increase of process efficiency, a high density fed-batch process was developed, where concentrated medium is fed to the cells. Fed-batch process using concentrated medium was evaluated for its ability to improve cell growth and protease titer of T. turnirae. It was found to result in up to 3.9-fold increase in final protease activity compared to batch culture control